PENGARUH PRIVACY CONCERNS, ENTERTAINMENT dan PEER INFLUENCE TERHADAP ATTITUDE TOWARD SNA (SOCIAL NETWORKING ADVERTISING) - Randy Chandra (Universitas Mercu Buana, 2015)
This study aimed to identify the influence of Privacy Concerns, Entertainment and Peer Influence on Attitude toward SNA (Social Networking Advertising). With a total of 150 respondents were involved. This research conducted on students of the Faculty of Economics and Business, University of Mercu Buana using SEM Lisrel 8.7 for data processing. The results of processing obtained Privacy Concerns T-value = 2.36, Entertainment T-value = 2.85 and Peer Influence T-value = 3.50 all variables here significant effect on Attitude toward SNA (Social Networking Advertising).Keywords: Privacy Concerns, Entertainment dan Peer Influence